Baabwaa and Wooliam - Sweet, Melissa (Somerville, MA : Candlewick Press, 2017)
Baabwaa and William are friends, and together they decide to have an adventure of their own. After meeting a fierce wolf in sheeps wool they form an unusual friendship with the wolf, teaching him to read and knit. They also lose a little weight.
AD530L
Decoding demand: 73 (high)
Semantic demand: 89 (very high)
Syntactic demand: 67 (high)
Structure demand: 81 (very high)
Accelerated Reader AR
Keywords: Friendship -- Juvenile fiction; Sheep -- Juenile fiction; Wolves -- Juvenile fiction; Picture books for children